The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/min8030120
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Infrared Spectroscopy to Determine the Quality of Carbonate-Rich Diatomite Ores

Abstract: Diatomite, a rock formed by the accumulation of opaline diatom frustules, is a preferred raw material for the manufacturing of filters. Its uniqueness relies on the high porosity and inertness of the frustules. The presence of carbonates in some diatomite ores hinders these properties. The purpose of this study was to identify the type of carbonates and their association with the ore in a diatomite deposit, and to assess the suitability of determining the quality of the ore using techniques with potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…The FTIR spectra of the heated KBr-pellets are shown in Figure 2. The identification of minerals and absorption bands were performed in accordance with the recommendations of: Farmer [21] and Zviagina et al [22] for glauconite; Madejova and Komadel [23,24] for bentonite; and Smith [25] and Guatame-Garcia and Buxton [26] for diatomite.…”
Section: Mineral Sorbents Characterizationmentioning
confidence: 99%
“…The FTIR spectra of the heated KBr-pellets are shown in Figure 2. The identification of minerals and absorption bands were performed in accordance with the recommendations of: Farmer [21] and Zviagina et al [22] for glauconite; Madejova and Komadel [23,24] for bentonite; and Smith [25] and Guatame-Garcia and Buxton [26] for diatomite.…”
Section: Mineral Sorbents Characterizationmentioning
confidence: 99%
“…The second most abundant element in DE is Si (37%) as was expected and elsewhere reported (Yuan et al, 2010). The Si content varies depending on the physicochemical conditions present during the formation of the DE bank (Guatame-Garcia, Buxton, 2018). These minor variations could affect the performance of the material because the higher the content of Si the more silanol groups available to react with polar organic compounds increasing the number of compounds adsorbed by DE (Al-Ghouti et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…These minor variations could affect the performance of the material because the higher the content of Si the more silanol groups available to react with polar organic compounds increasing the number of compounds adsorbed by DE (Al-Ghouti et al, 2003). Carbonate minerals can also affect the number of compounds that DE can absorb because the deposit of this material along the diatomite structure reduces its porosity (Guatame-Garcia, A. Buxton, 2018). However, the XRD analysis showed several crystal structures formed in the DE with the abundance of cristobalite, tridymite, and quartz, but anyone with carbonate which ensures the condition of the material to be a practical support to the nanoparticles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MWIR region of the electromagnetic spectrum is under-investigated due to limited instrumental development. However, recent studies [30,31] showed that the MWIR region of the electromagnetic spectrum has a good potential for the characterization of materials.…”
Section: Introductionmentioning
confidence: 99%